1993
DOI: 10.1515/znc-1993-3-419
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II: Thermodynamics and Kinetics of Electron Transport from QA - to QB(QB - ) and Deleterious Effects of Copper(II)

Abstract: Studies on thermodynamics and kinetics of electron transfer from QA- to QB(QB-) were performed by monitoring laser flash induced changes of the relative fluorescence emission as a function of temperature (220 K < T < 310 K) in isolated thylakoids and PS II membrane fragments.In addition, effects of bivalent metal ions on PS II were investigated by measuring conventional fluorescence induction curves, oxygen evolution, manganese content and atrazine binding mostly in PS II membrane fragments. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 11 publications
9
49
0
Order By: Relevance
“…The data reveal a further hydration-sensitive transition between above 310 K that was attributed to the detachment of the oxygen evolving complex. Figure 4 also shows the temperature dependence of the Q A → Q B electron transfer efficiency in the PS II RC gathered from fluorescence quantum yield experiments [6]. A comparison with the QENS data of PS II membrane fragments suggests that there is a close correlation between the thermal activation of molecular dynamics and the electron transfer efficiency from Q A to Q B [10,13].…”
Section: Qens Studies Of Ps II Membranesmentioning
confidence: 95%
See 2 more Smart Citations
“…The data reveal a further hydration-sensitive transition between above 310 K that was attributed to the detachment of the oxygen evolving complex. Figure 4 also shows the temperature dependence of the Q A → Q B electron transfer efficiency in the PS II RC gathered from fluorescence quantum yield experiments [6]. A comparison with the QENS data of PS II membrane fragments suggests that there is a close correlation between the thermal activation of molecular dynamics and the electron transfer efficiency from Q A to Q B [10,13].…”
Section: Qens Studies Of Ps II Membranesmentioning
confidence: 95%
“…The three temperature ranges A, B, and C are discussed in the text. The electron transfer efficiency according to [6] is shown by a full red line. This figure is reprinted from [10] with permission.…”
Section: Qens Studies Of Ps II Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the material used and experimental methods applied, various binding sites of Cu 2+ within the quinone-Fe complex have been suggested. Copper has been found to affect the binding affinity of atrazine to PSII [40] and to modify the Q B pocket [16]. Flash--induced absorption spectroscopy studies have shown that the primary charge sep-…”
Section: Non-heme Ironmentioning
confidence: 99%
“…A possible direct interaction between copper and calcium at the oxidising side of PSII was also shown both in vitro (Sabat, 1996) and in vivo (Maksymiec and Baszynski, 1999). Additional effects of Cu(II) toxicity on both the donor side, affecting the Mn-cluster and the extrinsic proteins of the oxygen-evolving complex, and the acceptor side, interacting with the nonheme Fe 2+ have been reported (Renger et al 1993, Jegerschóld et al 1995, Sersen et al 1997. The interaction of Cu(II) toxicity with photoinhibitory and recovery proceses on PSII has been also investigated (Yruela et al 1996b, Pätsikkä et al 1998 It is also needs to be established which physiological effects of copper on photosynthesis in vivo result from inhibition of the electron transport on PSII.…”
Section: Introductionmentioning
confidence: 85%